Narratives in an authoritarian environment: Narrative strategies, plots, and characters in Moscow's public transport reforms debate. Issue 2 (23rd September 2021) - Uldanov, Artem; Gabriichuk, Tatiana; Karateev, Dmitry; Makhmutova, Maria
Abstract: This article draws on the Narrative Policy Framework (NPF) to analyze the recent debates over Moscow's public transport policy. Despite a proliferation of NPF implementations in recent years, applications in authoritarian institutional settings remain rare. We seek to fill this gap by examining how the actors combine narrative strategies, characters, and plots to advocate their vision of public transport development in Moscow. To this end, this study tests NPF meso‐level hypotheses on narrative strategies and their connections with plots and characters used in the context of Russian electoral authoritarian regime. The results show that the NPF hypotheses are applicable for the analysis of policy debates in an authoritarian context. While the governmental coalition uses an angel shift strategy—focusing on heroes, beneficiaries, and stories of control—to contain the scope of conflict, the opposing coalition implies a devil shift strategy with a specific attention to villains, victims, and different plots to expand the scope of conflict. 摘要: 本文基于叙事政策框架 (NPF), 分析近年来关于莫斯科公共运输政策的辩论。尽管近年来NPF的应用得以扩散, 但在威权主义制度背景中的应用情况仍然很少。我们通过分析行动者如何结合叙事策略、角色和情节以期倡导各自的莫斯科公共运输发展愿景, 进而填补该研究空白。为此, 本研究检验了俄罗斯选举威权主义制度情境下NPF的中观层面假设, 这些假设有关于叙事策略以及叙事策略与情节和角色的联系。研究结果表明, NPF假设适用于威权主义情境下的政策辩论分析。政府联盟使用"美化政治盟友" (angel shift) 的策略, 聚焦于正面人物、受益者和控制叙事, 以期抑制冲突范围, 而反对联盟使用了"丑化政治对手" (devil shift) 的策略, 具体关注反面人物、受害者和不同情节, 以期扩大冲突范围。 Resumen: Este artículo se basa en el Narrative Policy Framework (NPF) para analizar los debates recientes sobre la política de transporte público de Moscú. A pesar de la proliferación de implementaciones de NPF en los últimos años, las aplicaciones en entornos institucionales autoritarios siguen siendo raras. Buscamos llenar este vacío examinando cómo los actores combinan estrategias narrativas, personajes y tramas para defender su visión del desarrollo del transporte público en Moscú. Con este fin, este estudio prueba hipótesis de nivel meso del NPF sobre estrategias narrativas y sus conexiones con tramas y personajes utilizados en el contexto del régimen autoritario electoral ruso. Los resultados muestran que las hipótesis NPF son aplicables para el análisis de debates políticos en un contexto autoritario. Mientras que la coalición gubernamental utiliza una estrategia de cambio de ángeles, centrándose en héroes, beneficiarios e historias de control, para contener el alcance del conflicto, la coalición opuesta implica una estrategia de cambio del diablo con una atención específica a los villanos, las víctimas y las diferentes tramas. para ampliar el alcance del conflicto.